Identifikácia rentgenových zdrojov v optickom obore - Kocka, Matúš; Hroch, Filip; Masarykova univerzita. Přírodovědecká fakulta. Fyzikální sekce (2007)
Práca sa zaoberá spôsobmi identifikácie optických náprotivkov rentgenových zdrojov objavených družicami INTEGRAL a Swift. Tiež sa venuje analýze fluktuácií jasnosti týchto objektov, farebným indexom a svetelným krivkám.
Goal of our thesis is to find optical counterparts of selected X-ray and gamma sources measured by INTEGRAL and Swift space missions. Our work also provides basic measurement of short-term variations of sources in optical band, as well as its colour curve and light curve analysis.
Vedoucí práce: Filip Hroch
Bakalářská práce (Bc.)--Masarykova univerzita, Přírodovědecká fakulta, 2008
Keywords: aplikovaná fyzika; astrofyzika; applied physics; astrophysics; bakalářské práce